Roles of microRNAs in multiple organs under mycotoxin stress by bioinformatic analysis - Eun Jung Sohn; Kun-Taek Park (Poultry Science)
Mycotoxins are naturally produced by certain fungi and are common food contaminants that endanger human health and well-being worldwide. They have broad implications, including roles in carcinogenesis, which is often fatal. Therefore, identifying new biomarkers of mycotoxin activity and enabling early diagnosis of mycotoxin-induced diseases is critical. MicroRNAs (miRNAs) are post-transcriptional regulators of gene expression and influence different physiological processes, including those involved in heart disease, cancer, and apoptosis. Furthermore, miRNAs are often involved in mycotoxin-induced toxicity and respond to various environmental factors. In this review, we discuss the miRNAs altered in response to important mycotoxins in several organisms, with a focus on the predicted biological roles and targets of miRNAs regulated by two common mycotoxins: aflatoxin B1 and ochratoxin A. This review aims to serve as a resource for researchers and scientists working to understand the molecular mechanisms underlying mycotoxin toxicity and developing targeted interventions to prevent and control mycotoxin-induced damage to various organs.